Development of Problem-Based Learning E-Module to Enhance Students’ Critical Thinking on Acid-Base Material - Daulay, Nala Angriani Syalsabila; Sugiharti, Gulmah (Jurnal Inovasi Pembelajaran Kimia, 2025)
Acid-base concepts are often abstract and difficult for students to understand, limiting the development of their critical thinking skills. At SMAS An-Nizam Medan, current learning models have not been fully effective in promoting student engagement or enhancing these skills. This study aims to develop a Problem-Based Learning (PBL) e-module to improve students’ critical thinking and to evaluate its validity and practicality. The research uses a Research and Development (R&D) method based on the Borg and Gall model, limited to the seventh stage. The participants consisted of two chemistry lecturers (as media and material experts), one chemistry teacher, and students from Class XI Al-Khawarizmi at SMAS An-Nizam Medan. Data were collected using a questionnaire adapted from BSNP standards. The results showed that the PBL-based e-module was valid, with an average score of 85.75% from material experts, 95.48% from media experts, and 100% from the teacher classified as highly valid. Student responses showed a practicality score of 87.97%, indicating that the module is very practical. In conclusion, the developed PBL-based e-module is valid and practical, making it suitable for use in teaching acid-base chemistry material to support the development of students’ critical thinking skills.